RETRACTED: Silicon phase origin on glassy carbon in KF-KCl-K2SiF6 fusion - S. I. Zhuk; L. M. Minchenko; O. V. Chemezov; V. B. Malkov; A. V. Isakov; Yu. P. Zaikov (Chimica Techno Acta)
Following the joint decision of the Editor-in-Chief and the journal's Ethics Committee, this article has been retracted. The article (its original Russian version) is an erroneously published duplicate of a paper that has already been published in Chimica Techno Acta 2014;1(2):67-72, doi:10.15826/chimtech.2014.1.2.1047. One of the conditions of submission of a paper for publication is that a paper has not been published previously. As such this article represents a severe abuse of the scientific publishing system. Our Editorial Board takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process.